Pengembangan Handout Materi Biologi SMP Berbasis Pendekatan Konsep pada Sistem dalam Kehidupan Manusia - Ali Mustofa; Imas Cintamulya (Universitas Sebelas Maret, 2017)
The purpose of this research is to develop the handout of biology system material in human life which is valid, practical and effective. The development of handouts uses a conceptual approach, so the presentation of the material is prepared with the core of a material concept. The development model used using Borg and Gall models. The steps of Borg and Gall model development consists of 10 stages: 1) Research and data collection; 2) Planning; 3) Development of product draft; 4) Initial field trials; 5) Revise test results; 6) Field trials; 7) Improvement of product of field test result; 8) Field implementation test; 9) Completion of the final product; 10) Dissemination and implementation. However, based on the limitations of this development the researcher did not use steps 4, 7, 8, and 9. The data collection techniques used validation sheet instrument, observation sheet, test sheet and questionnaire. This research trial was conducted in SMP Negeri 7 Tuban, as many as 20 students in class VIII. From the validation results of material experts and media experts obtained a value of 78 with valid categories. While the results of practicality test obtained value 93.75% with very practical category. Average questionnaire of student response to the use of this handout of 89.8% with very effective category. Based on the results of students' learning mastery obtained an average of 85% Based on the results of questionnaire responses obtained students average student achievement response rate was 89%. While based on the observation of student activity shows the average value of each aspect in accordance with the criteria values specified in the effective category. Thus it can be concluded that handout in classification is valid, practical and effective in implementation aspect and proper to be used as learning media for student